DESIGN OF A BUILDING DESIGN, MODELING, AND INFORMATION (DPIB) LABORATORY AS A LEARNING FACILITY AT SMK NEGERI 5 PADANG - Barkhia Yunas; Mutia Alius; Yuni Purnama Syafri; Dyla Midya Octavia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
The availability of a laboratory that supports the characteristics of practical learning is an important factor in developing students’ competencies in Building Design, Modeling, and Information (DPIB). This community service activity aimed to develop a functional and comfortable DPIB laboratory design at SMK Negeri 5 Padang to support technology-based learning. The activity employed a participatory and user-centered design approach through several stages, including existing-condition observation, identification of partner needs, conceptual design, design development, validation, and finalization. The activity resulted in a laboratory design with an area of approximately 270 m², integrating a planning and model-making practice area, instructor room, computer-based design practice area, circulation system, lighting, ventilation, electrical facilities, and digital learning support. The proposed design provides the school with a technical reference for developing a more structured DPIB laboratory that is aligned with the needs of vocational learning.